Combined de‐repression of chemoresistance associated mitogen‐activated protein kinase 14 and activating transcription factor 2 by loss of microrna‐622 in hepatocellular carcinoma - Fritz, Valerie; Malek, Lara; Gaza, Anne; Wormser, Laura; Appel, Majken; Kremer, Andreas; Thasler, Wolfgang E.; Neurath, Markus; Hellerbrand, Claus; Boßerhoff, Anja Katrin; Dietrich, Peter; Siebler, Jürgen (Cancers, 2021)
Chemoresistance is a major hallmark driving the progression and poor prognosis of hepatocellular carcinoma (HCC). Limited chemoresponse of HCC was demonstrated to be mediated by mitogen‐activated protein kinase 14 (MAPK14) and activating transcription factor 2 (ATF2). Recently, we have demonstrated loss of control of RAS‐RAF‐ERK‐signaling as a consequence of miR‐622 downregulation in HCC. However, the majority of target genes of this potent tumorsuppressive microRNA had remained elusive. The MAPK14‐ATF2‐axis represents a collateral pathway ensuring persisting ERK‐activation in the presence of sorafenib‐mediated RAF-inhibition. In contrast to the function of the MAPK14‐ATF2‐axis, both the expression and regulation of MAPK14 and ATF2 in human HCC remained to be clarified. We found combined overexpression of MAPK14 and ATF2 in human HCC cells, tissues and in sorafenib resistant cell lines. High expression of MAPK14 and ATF2 was associated with reduced overall survival in HCC patients. Deciphering the molecular mechanism promoting combined upregulation of MAPK14 and ATF2 in HCC, we revealed that miR‐622 directly targets both genes, resulting in combined de‐repression of the MAPK14‐ATF2‐axis. Together, miR‐622 represents a superior regulator of both RAS‐RAF‐ERK as well as MAPK14‐ATF2‐signaling pathways in liver cancer.
CRIS-Team Scopus Importer:2021-03-19
Keywords: HCC; Hepatocellular carcinoma; Liver cancer; MAPK14; MicroRNA; MiR‐622; RAS

Identification of novel targets of miR-622 in hepatocellular carcinoma reveals common regulation of cooperating genes and outlines the oncogenic role of zinc finger CCHC-type containing 11 - Gaza, Anne; Fritz, Valerie; Malek, Lara; Wormser, Laura; Treiber, Nora; Danner, Johannes; Kremer, Andreas E.; Thasler, Wolfgang E.; Siebler, Jürgen; Meister, Gunter; Neurath, Markus F.; Hellerbrand, Claus; et al. (Neoplasia, 2021)
The poor prognosis of advanced hepatocellular carcinoma (HCC) is driven by diverse features including dysregulated microRNAs inducing drug resistance and stemness. Lin-28 homolog A (LIN28A) and its partner zinc finger CCHC-type containing 11 (ZCCHC11) cooperate in binding, oligouridylation and subsequent degradation of tumorsuppressive let-7 precursor microRNAs. Functionally, activation of LIN28A was recently shown to promote stemness and chemoresistance in HCC. However, the expression and regulation of LIN28A in HCC had been unclear. Moreover, the expression, regulation and function of ZCCHC11 in liver cancer remained elusive. In contrast to "one-microRNA-one-target" interactions, we identified common binding sites for miR-622 in both LIN28A and ZCCHC11, suggesting miR-622 to function as a superior pathway regulator. Applying comprehensive microRNA database screening, human hepatocytes and HCC cell lines, patient-derived tissue samples as well as "The Cancer Genome Atlas" (TCGA) patient cohorts, we demonstrated that loss of tumorsuppressive miR-622 mediates derepression and overexpression of LIN28A in HCC. Moreover, the cooperator of LIN28A, ZCCHC11, was newly identified as a prognostic and therapeutic target of miR-622 in liver cancer. Together, identification of novel miR-622 target genes revealed common regulation of cooperating genes and outlines the previously unknown oncogenic role of ZCCHC11 in liver cancer.
CRIS-Team Scopus Importer:2021-05-07
Keywords: drug resistance; HCC; Hepatocellular carcinoma; microRNA; ZCCHC11

Molecular cross-talk between Y5-receptor and neuropeptide Y drives liver cancer - Dietrich, Peter; Wormser, Laura; Fritz, Valerie; Seitz, Tatjana; de Maria, Monica; Schambony, Alexandra; Kremer, Andreas; Günther, Claudia; Itzel, Timo; Thasler, Wolfgang E.; Teufel, Andreas; Trebicka, Jonel; et al. (Journal of Clinical Investigation, 2020)
Hepatocellular carcinoma (HCC) is clearly age-related and represents one of the deadliest cancer types worldwide. Due to globally increasing risk factors including metabolic disorders, the incidence rates of HCC are still rising. However, the molecular hallmarks of HCC remain poorly understood. Neuropeptide Y (NPY) and NPY-receptors represent a highly conserved, stress-activated system which is involved in diverse cancer-related hallmarks including aging and metabolic alterations, but its impact on liver cancer had been unclear. Here, we observed increased NPY5-receptor (Y5R) expression in HCC which correlated with tumor growth and survival. Furthermore, we found that its ligand NPY was secreted by peri-tumorous hepatocytes. Hepatocyte-derived NPY promoted HCC progression by Y5R-activation. Transforming growth factor beta 1 (TGFβ1) was identified as a regulator of NPY in hepatocytes and induced Y5R in invasive cancer cells. Moreover, NPY-conversion by dipeptidylpeptidase 4 (DPP4) augmented Y5R-activation and function in liver cancer. The TGFβ-NPY-Y5R-axis and DPP4 represent attractive therapeutic targets for controlling liver cancer progression.
EVALuna2:212290
Keywords: Aging; Cancer; Hepatology

Neuroblastoma RAS Viral Oncogene Homolog (NRAS) Is a Novel Prognostic Marker and Contributes to Sorafenib Resistance in Hepatocellular Carcinoma - Dietrich, Peter; Gaza, Anne; Wormser, Laura; Fritz, Valerie; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Neoplasia, 2019)
Inhibition of the RAS-RAF-ERK-pathway using sorafenib as a first-line and regorafenib as a second-line treatment approach is the only effective therapeutic strategy for advanced hepatocellular carcinoma (HCC). Recent studies suggest that wild-type KRAS and HRAS isoforms could majorly contribute to HCC progression and sorafenib resistance. In contrast, the role of neuroblastoma RAS viral oncogene homolog (NRAS) in HCC remained elusive. In this study, wild-type NRAS was found to be overexpressed in HCC cell lines, preclinical HCC models, and human HCC tissues. Moreover, NRAS overexpression correlated with poor survival and proliferation in vivo. However, siRNA-pool-mediated NRAS knockdown showed only slight effects on HCC proliferation, clonogenicity, and AKT activity. We determined that KRAS upregulation served as a functional compensatory mechanism in the absence of NRAS, which was overcome by combined inhibition of NRAS and KRAS in HCC cells. Furthermore, NRAS expression was elevated in sorafenib-resistant compared to nonresistant HCC cells, and NRAS knockdown enhanced sorafenib efficacy in resistant cells. In summary, NRAS appears to be a prognostic marker in HCC and contributes to sorafenib resistance. Regarding potential therapeutic strategies, NRAS inhibition in HCC should be combined with KRAS inhibition to prevent KRAS-mediated rescue effects.
CRIS-Team WoS Importer:2019-03-20